2013
DOI: 10.1091/mbc.e12-12-0856
|View full text |Cite
|
Sign up to set email alerts
|

Dual-color superresolution microscopy reveals nanoscale organization of mechanosensory podosomes

Abstract: Podosomes are multimolecular mechanosensory structures with a protrusive actin core and an adhesive ring of integrins and adaptor proteins. Dual-color direct stochastic optical reconstruction microscopy is used to reveal the nanoscale localization of the ring components αMβ2 integrin, talin, and vinculin with respect to the actin core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 50 publications
7
114
1
Order By: Relevance
“…33,34 Strikingly, the application of high-resolution imaging revealed that the podosome ring shows a discontinuous organization and in fact consists of individual clusters that surround the core. [35][36][37] Recent work also revealed the existence of a third substructure at podosomes, the so-called "cap," which localizes on top of the podosome and partially overlaps with core and ring structures. To date, only a few cap proteins have been identified, including the myosin-binding protein supervillin 32 and the formin FMNL-1.…”
Section: Podosomes In 2dmentioning
confidence: 99%
See 2 more Smart Citations
“…33,34 Strikingly, the application of high-resolution imaging revealed that the podosome ring shows a discontinuous organization and in fact consists of individual clusters that surround the core. [35][36][37] Recent work also revealed the existence of a third substructure at podosomes, the so-called "cap," which localizes on top of the podosome and partially overlaps with core and ring structures. To date, only a few cap proteins have been identified, including the myosin-binding protein supervillin 32 and the formin FMNL-1.…”
Section: Podosomes In 2dmentioning
confidence: 99%
“…32 Work on the function of podosomes has progressed steadily during the last decade. It is now well-accepted that they act as (1) adhesive structures, 37,46 (2) mechanosensors and-transducers, 37,47 and (3) are able to degrade extracellular matrix. 42,49 Evidence for these functions is based on (1) the presence of integrins and other ECM receptors, such as the hyaluronic acid receptor CD44 at podosomes, 47,[50][51][52] and (2) the ability of podosome components to act as mechanotransducers by converting mechanical cues into chemical signals.…”
Section: M-csfmentioning
confidence: 99%
See 1 more Smart Citation
“…Podosomes, in turn, contain a central actin core, about 200 nm in diameter, oriented perpendicularly to the plasma membrane and several micrometres high [10]. The actin core of individual podosomes is surrounded by a peripheral adhesion ring, 0.5-1 mm in diameter, containing integrins and associated plaque proteins that mediate the adhesion to the bone surface [18][19][20][21][22][23]. The unique structure of podosomes, combined with their rapid turnover [18,24] and assembly into coherent SZ & 2017 The Author(s) Published by the Royal Society.…”
Section: Introductionmentioning
confidence: 99%
“…Podosomes are F-actinrich cone-shaped structures of B600 nm height and submicron diameter, located at the basal face of cells, perpendicular to, and in contact with the substratum via integrins at the podosome ring 8,9 . Recently, super-resolution imaging of the adhesion ring revealed that its components are organized in clusters forming a polygonal structure [10][11][12] . Podosomes are regularly spaced and interconnected through a radial F-actin network 13,14 .…”
mentioning
confidence: 99%